HUBUNGAN PENGETAHUAN IBU TENTANG POSYANDU DENGAN MOTIVASI IBU DATANG KE POSYANDU 1,2 DI DESA BANTERAN KECAMATAN SUMBANG TAHUN 2008 - Novi Diyah Pipit Ratna Sari; Indri Heri Susanti (Viva Medika, 2008)
Background: Knowledge plays an important role in determining the behaviors that influence maternal motivation to come to Posyandu because Posyandu is oneway easier to know the mother and toddler infant growth. In the village ofBanteran the number of infants who come to posyandu quite low at 60.6%. Objective: To determine the relationship between maternal knowledge aboutposyandu with maternal motivation come to Posyandu in the village of the DistrictBanteran Contribute in 2008. Methods: The study is an analytic correlation with cross-sectional approach. Thepopulation is mothers who have babies in the village of the District BanteranContribute Banyumas regency totaling 736 people. Sampling is done by clusterrandom sampling with 74 people. The research instrument used questionnairesand data analysis with Spearman Rank correlation test with significance level of0.05. Results: Of the 74 respondents who have knowledge of both categories posyandumany as 37 people (50.0%). And of the 74 respondents were motivated to come toPosyandu high category as many as 44 people (59.5%). Spearman RankCorrelation test results are known r-value calculated at 0,433dan p-value of0.000 (<relationship between maternal knowledge about posyandu with maternalmotivation to come to Posyandu. The relationship obtained (0.433) included inthe category of moderate because of the value of r-count is in the range from 0.40to 0.559. Conclusion: There is a relationship between mother's knowledge on workmotivation and motivation posyandu mother to come to Posyandu.